2016
DOI: 10.1007/s41669-016-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Pharmaceutical Prices for Economic Evaluations When There Is No Market: A Review

Abstract: BackgroundEconomic evaluation helps policy makers and healthcare payers make decisions on drug listing, coverage, and reimbursement. When economic evaluations are conducted before a product launch, the prices of the pharmaceuticals have to be forecast.ObjectiveThe aim of this study was to examine the methods of establishing proxy prices and their accuracies compared with actual market prices after the product launch.MethodsWe searched the literature for evaluations for drugs that were licensed in the US betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…the average absolute value of the ( A  −  E )/ E index for a method based on a close substitute and others equalled—after correction—84 and 45%, respectively. Those values in the study of Akpinar et al [1] were 68 and 80%, respectively, indicating slightly better performance of the method using the price of a close substitute. That conclusion no longer holds true after the adjustment.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…the average absolute value of the ( A  −  E )/ E index for a method based on a close substitute and others equalled—after correction—84 and 45%, respectively. Those values in the study of Akpinar et al [1] were 68 and 80%, respectively, indicating slightly better performance of the method using the price of a close substitute. That conclusion no longer holds true after the adjustment.…”
mentioning
confidence: 89%
“…In their publication in Pharmacoeconomics Open , Akpinar et al [1] reported the results of their review of methods for forecasting drug prices for economic evaluations. This was an interesting article, and I agreed with most of the conclusions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We then developed a hierarchical method to identify the unit price of each drug used in study trials (9). Firstly, we used the Alberta Health Drug Benefit List (ADBL) (10) to provide a market dollar value for a unit of the drug in the trial (32 drugs).…”
Section: Estimating the Contribution Of Industryprovided Drugs -Trialmentioning
confidence: 99%